2014
DOI: 10.1016/j.spen.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Malnutrition and Neurologic Disability in Africa

Abstract: Malnutrition and neurodisability are both major public health problems in Africa. This review highlights key areas where they interact. This happens throughout life and starts with maternal malnutrition affecting fetal neurodevelopment with both immediate (eg, folate deficiency causing neural tube defects) and lifelong implications (eg, impaired cognitive function). Maternal malnutrition can also increase the risk of perinatal problems, including birth asphyxia, a major cause of neurologic damage and cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 52 publications
0
82
0
4
Order By: Relevance
“…9 Our results show that children with CFD also have higher prevalence of stunting and underweight compared with those with no CFD functional difficulties. Internationally, there is a growing interest in the links between nutrition and disability 10,11 as countries with high levels of malnutrition and nutrient deficiency also often report higher rates of disability and developmental delay. 12 While results do not allow to establish a causality between the two, it is likely that an overlap exists, and that malnutrition can contribute to a variety of different disabilities and that, in turn, disability and functional difficulties can contribute to malnutrition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Our results show that children with CFD also have higher prevalence of stunting and underweight compared with those with no CFD functional difficulties. Internationally, there is a growing interest in the links between nutrition and disability 10,11 as countries with high levels of malnutrition and nutrient deficiency also often report higher rates of disability and developmental delay. 12 While results do not allow to establish a causality between the two, it is likely that an overlap exists, and that malnutrition can contribute to a variety of different disabilities and that, in turn, disability and functional difficulties can contribute to malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…12 While results do not allow to establish a causality between the two, it is likely that an overlap exists, and that malnutrition can contribute to a variety of different disabilities and that, in turn, disability and functional difficulties can contribute to malnutrition. 10 For instance, malnutrition can cause disability from pregnancy onwards, through maternal malnutrition both during the prenatal 13 and postnatal period. 14 Additionally, macro and micro nutrients deficiency during infancy and childhood have also been linked to higher disability risk.…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, she can only consume small amounts of food or liquid as most of it spills from her mouth during feeding. Konje and Ladipo (2000), Kerac et al (2014) and Wu et al (2010) have reported malnutrition as a cause of disability. However, few researchers have explored alternative relationships between disability and nutrition such as the intersectionality between disability and feeding and swallowing.…”
Section: Disability and Food Securitymentioning
confidence: 99%
“…Anak berkebutuhan khusus yang tidak tercukupi asupan energinya dari makanan akan lebih berisiko untuk menderita kondisi sekunder lain seperti kurang gizi, defisiensi zat gizi mikro, dan gizi buruk (8). Selain itu, ABK juga cenderung memiliki risiko kehilangan zat gizi dan angka kecukupan gizi yang lebih tinggi (9). Oleh karena itu, pemenuhan asupan energi dari makanan pada ABK, termasuk anak mencapai status gizi dan kesehatan yang optimal.…”
Section: Bahan Dan Metodeunclassified